1995
DOI: 10.1136/gut.37.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Low dose famotidine and cimetidine in single postprandial doses: a placebo controlled comparative study of overnight pH.

Abstract: To investigate the relative abilities of low doses of famotidine and cimetidine to raise intragastric pH after a single postprandial evening dose, 16 healthy volunteers were recruited to a four period crossover trial of famotidine 10 mg, cimetidine 100 mg and 200 mg compared with placebo. Intragastric pH was monitored between 1800 and 0730 with a nasogastric pH electrode. Median gastric pH rose from 1.35 (interquartile range 1-1-1-65) with placebo to 1 95 (1.6-5.35, p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In this study, the gastric acid inhibitory effect of ranitidine, 75 mg, and famotidine, 10 mg, taken around midday, persisted even in the overnight period. Overall, the effects of ranitidine and famotidine were similar and consistent with previous studies which have evaluated low doses of famotidine and ranitidine 3–6 , . 16 However, it is uncertain whether this late and modest effect can translate into symptomatic benefit for patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the gastric acid inhibitory effect of ranitidine, 75 mg, and famotidine, 10 mg, taken around midday, persisted even in the overnight period. Overall, the effects of ranitidine and famotidine were similar and consistent with previous studies which have evaluated low doses of famotidine and ranitidine 3–6 , . 16 However, it is uncertain whether this late and modest effect can translate into symptomatic benefit for patients.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have compared the onset and duration of action of ranitidine, famotidine and cimetidine on intragastric acidity using the model of 24‐h acidity 3–6 . This model was designed for the study of the effect of these drugs on gastric acidity by attempting to simulate normal everyday activity.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of low doses of H 2 ‐antagonists as OTC treatments for nocturnal heartburn and dyspepsia offers a potential solution to this problem, because of their long duration of action 16 , . 17 So far, no studies exist comparing these two medication groups at OTC dosages for patients with nocturnal heartburn.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have, however, demonstrated that at over-the-counter doses, cimetidine has a slightly lower antisecretory ef®cacy than famotidine and ranitidine. 9,11 On the other hand, a new effervescent preparation of 200 mg cimetidine has been shown to induce a more rapid suppressive effect on intragastric acidity than ®lm-coated tablets of famotidine. 31 This is likely to induce a more rapid symptom relief during the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the efficacy of the H 2 ‐antagonists at over‐the‐counter dosage were usually performed either in fasting or postprandial subjects 6 –11 . It is well known that meal intake reduces the acid inhibitory effect of high dose H 2 ‐antagonists 12 –14 .…”
Section: Introductionmentioning
confidence: 99%